2018
DOI: 10.1155/2018/2907812
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dietary Related Factors of Recurrent Aphthous Stomatitis among College Students

Abstract: Objective We investigated the occurrence of recurrent aphthous stomatitis (RAS) among college students and its potential influence by dietary habits. Methods Study of dietary habits and RAS among students in Beijing University of Chinese Medicine was carried by homemade questionnaire. Multivariate binary logistic regression analysis was used to identify RAS risk factors and explore their relations. Results Among 1011 investigated college students, family history (odds ratio (OR) 1.678, 95% confidence intervals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 16 publications
5
21
0
5
Order By: Relevance
“…Consistent with previous observational studies (Ma et al, 2015;Du et al, 2018), we also found that insomnia has a causal effect to increase the risk of mouth ulcers. Insomnia will lead to late bedtime, which can disturb the secretion of hormones, such as growth hormone, cortisol, and adrenocorticotropic hormone (Ma et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous observational studies (Ma et al, 2015;Du et al, 2018), we also found that insomnia has a causal effect to increase the risk of mouth ulcers. Insomnia will lead to late bedtime, which can disturb the secretion of hormones, such as growth hormone, cortisol, and adrenocorticotropic hormone (Ma et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…The total rate of Xerostomia among RAS patients was 45.8%; and it was 79% among major RAS patients with significant associated OR= 3.3 times, 95%CI =1.0-11.4, p=0.04) (Table 6). This result is in agreement with others studies that reported a significant association between Xerostomia and RAS [26,27]. This result can be explained by the fact that almost all of potential factors of RAS occur combine with another symptom which is mouth dryness (Xerostomia), which might be having a role in RAS occurrence.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the prevalence of RAS was 55% and 35.6% discovered in the dental clinic as of 2010–2012 and 2014-2015, respectively [ 1 , 2 ]. Other studies carried out in the midst of the population of 18-year-old adolescents in Brazil discovered to be 24.9% [ 3 ], about 10.84% RAS were also discovered in Turkey [ 4 ], 14% was reported in the female dental students in King Khalid University Saudi Arabia [ 5 ], and 29.38% was reported in the college students in Beijing University of Chinese Medicine [ 6 ]. RAS is considered as a multifactorial process of unknown etiology, in which various triggering factors and an immunological disturbance are combined, including genetic [ 7 , 8 ], vitamin B-12, folate, and iron deficiency [ 9 , 10 ] and an allergic condition, such as atopy [ 11 , 12 ] Pain or unpleasant feeling and its recurrency in the oral cavity are always complained by an individual that has RAS, and this condition makes researchers interested in discovering the pathogenesis of RAS and its ultimate goal in finding the appropriate novel therapy [ 13 ].…”
Section: Introductionmentioning
confidence: 99%